2000
DOI: 10.3406/galip.2000.2172
|View full text |Cite
|
Sign up to set email alerts
|

Animaux domestiques, bêtes sauvages et objets en matières animales du Rubané au Michelsberg : de l'économie aux symboles, des techniques à la culture

Abstract: AnimAux domestiques, bêtes sAuvAges et objets en mAtières AnimAles du rubAné Au michelsberg De l'économie aux symboles, des techniques à la culture

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
10

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 12 publications
0
11
0
10
Order By: Relevance
“…Sheep/goats and cattle occupy an essential place: in five cases out of six they represent at least two-thirds of the faunal spectrum (Table 2). In general the middle Neolithic is characterized in France by the low importance of hunting in the economy (Poulain, 1984;Arbogast et al, 1991;Jeunesse and Arbogast, 1997;Sidéra, 2000Sidéra, , 2003Blaise et al, 2009). More precisely, it is noticeable that sheep and goats dominate at least by half the faunal spectra of the three cave occupations, cattle representing respectively only 15.1%, 18.7% and 3.3% (Table 2).…”
Section: Some General Archaeozoological Datamentioning
confidence: 96%
See 1 more Smart Citation
“…Sheep/goats and cattle occupy an essential place: in five cases out of six they represent at least two-thirds of the faunal spectrum (Table 2). In general the middle Neolithic is characterized in France by the low importance of hunting in the economy (Poulain, 1984;Arbogast et al, 1991;Jeunesse and Arbogast, 1997;Sidéra, 2000Sidéra, , 2003Blaise et al, 2009). More precisely, it is noticeable that sheep and goats dominate at least by half the faunal spectra of the three cave occupations, cattle representing respectively only 15.1%, 18.7% and 3.3% (Table 2).…”
Section: Some General Archaeozoological Datamentioning
confidence: 96%
“…While the herding strategies for sheep and goats have begun to be relatively well known for south-western Europe at the beginning of the Neolithic (Jarman, 1976;Rowley-Conwy, 1991;Helmer, 1992;Helmer and Vigne, 2004;Helmer et al, 2005;Vigne and Helmer, 2007), our knowledge concerning cattle is still poor (e.g. Helmer, 1991a;Wilkens, 1991;Sana Segui, 1998, 2000Beeching et al, 2000;Vigne and Helmer, 1999;Tagliacozzo, 2005Tagliacozzo, -2006Bréhard, 2007). The complete archaeozoological analysis of four large Chassean open-air settlements, of the middle Rhône valley (Bréhard, 2007) and of the Aude valley (Bréhard, unpublished), has however shown that cattle did not play an insignificant role in the southern zone, either in economic or symbolic terms.…”
Section: Introductionmentioning
confidence: 97%
“…In practically all observed cases, figurative representations in Levantine rock art suggest that the use of the bow during the Neolithic could have been an exclusively male activity (Escoriza, 2002). In this sense, some authors have remarked that the hunting of medium to large size mammals is restricted in some societies to one social group (Escoriza and Piqu e, 2011;P erez-Ripoll, 1987;Senepart, 1993;Sidera, 2000). Ethnoarchaeological studies underline also the different roles between men and women in the choice of hunting technology (Lupo and Schmitt, 2005), highlighting the unusual participation of women in bow hunting (Bailey and Aunger, 1989) and the lack of involvement of women in the killing of large animals (Gurven and Hill, 2009), as they primarily hunt small and predictable game (Bliege and Bird, 2008).…”
Section: Discussion: Use and Role Of Neolithic Bowsmentioning
confidence: 97%
“…More specifically, different authors have pointed to a possible social role for hunting in European Neolithic societies, as a symbol of power and social status for some individuals. Reflected in the use of wild animal bones in ornaments; or in the frequent presence of arrowheads in the latest Neolithic burials (Vigne 1993; Sidéra 2000). This could be a possible explanation for the depiction of hunting scenes in the Levantine tradition, and also for the presence of deer as a decorative motif in some Bell‐Beaker ware in the Iberian Peninsula (Garrido and Muñoz 2000).…”
Section: Rock‐art and The Structuring Of A Neolithic Landscape The Cmentioning
confidence: 99%